(untitled) (Scientific journal of the Fergana State University, 2025)
This article explores the fact that the emphasis on education and upbringing in the world is a strategic requirement for a strong social policy, due to the conditions of today’s turbulent times. At a new stage of development of Uzbekistan, attention to the issue of education is taking a new level. This shows the effectiveness of achieving the consequentiality of the spiritual education strategy.